Derivation and validation of a search algorithm to retrospectively identify CRRT initiation in the ECMO patients - Guru, Pramod K.; Singh, Tarun D.; Passe, Melissa; Kashani, Kianoush B.; Schears, Gregory J; Kashyap, Rahul (Applied Clinical Informatics, 2016)
The role of extracorporeal membrane oxygenation (ECMO) in refractory cardiorespiratory failure is gaining momentum with recent advancements in technology. However, the need for dialysis modes such as continuous renal replacement therapy (CRRT) has also increased in the management for acute kidney injury. Establishing the exact timing of CRRT initiation in these patients from the electronic medical record is vital for automated data extraction for research and quality improvement efforts.We aimed to derive and validate an automated Electronic Health Records (EHR) search strategy for CRRT initiation in patients receiving ECMO.We screened 488 patients who received ECMO and a total of 213 patients underwent CRRT. We evaluated random 120 patients, 60 for derivation and 60 for validation cohorts. Following implementation of eligibility criteria, the algorithm was derived in 55 out of 120 ECMO/CRRT patients. The search algorithm was developed using first-time chart entry of ‘access pressure drop’ at CRRT initiation. The algorithm was then validated in an independent subset of 52 patients from the same time period. The overall agreement between electronic search algorithm and a comprehensive manual medical record review in the derivation and validation subsets, using ‘access pressure drop’ as the reference standard, was compared to assess CRRT initiation time.In the derivation subset (N=55), the automated electronic search strategy achieved an excellent agreement with manual search (D =0.99, 54 were identified electronically, and 55 upon manual review). There was no time difference observed in 49/54(89%) patients, while in the remaining 5 (9%) patients time difference was within 15 minutes. In the validation cohort (N=52), agreement was 100 % (D = 1.0, both methods identified 52 patients). Out of 52 patients, 47 (90%) had no time difference between the methods, for the remaining 5 (10%) patients, differences were within 15 minutes.The use of an electronic search strategy resulted in determining an accurate CRRT initiation time among ECMO patients.
Keywords: Continuous renal replacement therapy; extracorporeal membrane oxygenation; electronic health record; data extraction; quality improvement; research